GAMBARAN RESILIENSI AKADEMIK SISWA SMK DI MASA PANDEMI COVID-19 - RIOWATI, RIOWATI; MAULINA, MILANDAH (Jurnal Teknologi Pendidikan, 2022)
Abstract: This writing aim to discover the level of academic resilience of vocational students. The policy of online learning during the COVID-19 pandemic raises various challenges in all aspects of education, especially for students. The proper response to survive in pandemic conditions is needed by students to maintain the stabilization of the learning process. The researcher used a quantitative descriptive method with a sample of 220 vocational students from four majors selected using a simple random sampling technique. This study used the Academic Resilience Scale (ARS). The data analysis process is based on categorizing the maximum, minimum, mean, and standard deviation of academic resilience. The results of the categorization show that there are more students in the medium and high scores. It shows that vocational students during the pandemic have good academic resilience abilities, but the emotional ability score is low, and intervention is need.